Can Yoga Be Considered as an Effective Supportive Psychological Intervention with an Impact on the Quality of Life for Breast Cancer Survivors? - Eqdam Zamiri, Reza; Moqimi, Maynoosh; Shabani, Mina; Mazloomzadeh, Saeedeh; Valimoqaddam, Sahar; Dehnaei, Sediqe; Shajari, Zahra (Reports of Radiotherapy and Oncology, 2023)
Introduction: The aim of this study was to address the current lack of knowledge regarding the effects of yoga, an ancient oriental science, on reduction of stress and increase of Quality of Life (QoL) for breast cancer patients. Patients and methods: 27 breast cancer patients, who had completed their standard medical therapies, including surgery (modified radical mastectomy), chemotherapy and radiotherapy, were recruited from the Mehrane Charity Centre. The patients were randomly assigned to a yoga intervention group (n: 16) or a wait list (control group) (n: 11) for 32 sessions (16 weeks) of a yoga program. The pre- and post-yoga quality of life assessments for the patients were conducted using the Iranian Version of the EORTC QLQ-BR23 questionnaire. Results: After 16 weeks of yoga intervention and evaluation of physical, social, emotional, functional, sexual and body image well-being, it was revealed that our experimental group (mean age of 48.5±6.6 years old) had a significant decrease in emotional and sexual disturbance and experienced an improvement in positive body imaging compared with the control group (mean age: 46.9±8 years old) (P value<0.05). Furthermore, significant improvement in functional, emotional, and body image well-being was observed after yoga intervention in the experimental group in comparison to baseline condition (P value<0.05). Conclusion: Results of this study provide evidence for beneficial effects of a yoga program on the quality of life among breast cancer survivors.